Financial markets and ECB monetary policy communication - A second QE surprise - Martin Baumgärtner (Philipps-University Marburg, School of Business and Economics, 2022)
This paper shows that a different communication style of the European Central Bank (ECB) affects stock prices differently. A break in the ECB's communication from 2016 onwards makes it necessary to adjust the identification of monetary policy surprises in the euro area. By modifying the high-frequency identification of monetary policy shocks in the euro area, I can show that two quantitative easing shocks occur per decision: One during the release and one during the press conference. Although the impact on policy rates is identical, the release window shock seems to have a more pronounced effect on stock prices.
Keywords: E44; E52; E58; 330; Unconventional Monetary Policy; High-FrequencyData; ECB; Communication